Always Already Geopolitical: Trans Health Care and Global Tactical Technical Communication. (October 2019) - Edenfield, Avery C.; Colton, Jared S.; Holmes, Steve
Transgender persons face many barriers preventing them from accessing and receiving health care. Gender-transition care can be difficult because such care is frequently contingent upon geopolitics, such as location-based health-care policies that exclude transgender community attitudes and values. This article uses rhetorical cluster analysis to explore the combining two conceptual lenses—tactical technical communication and participatory localization—to study the do-it-yourself geopolitical medical literacies of transgender people in one Reddit forum. We found being trans online means to be tactical and geopolitical, encountering and negotiating geopolitical awareness of health-care options, exposing a privilege invisible to cisgender users.